IDENTIFICATION AND UTILIZATION OF THE SPECIES OF FERNS IN SEMPAYANG VILLAGE OF MALINAU BARAT - Nelsiani Thomas Sarira; Silfia Ilma; Fitri Wijarini (Borneo Journal of Biology Education (BJBE), 2025)
Ferns (Pteridophyta) are spore-bearing plants characterized by leaves that are circular when young (circinate vernation). This study aims to determine the types of ferns growing around the Sempayang village forest and their utilization by the local community. This study was conducted exploration methode with a survey. The survey was conducted to identify the types of ferns and their utilization. The study was conducted in Sempayang village, West Malinau district, from September to November 2022. The identification results consisted of 12 types of ferns, namely Asplenium nidus, Diplazium asperum, Deparia petersenii, Polypodium sp., Drynaria quicifolia, Sphenomeris sp., Nephrolepis hirsutula, Lyggodium circinatum, Dicranopteris linearis, Blechnum oriental, Adiantum latifolium, and Lygodium microphyluum. The Sempayang Village community utilizes the potential of ferns as vegetables, ornamental plants, and traditional medicine.